DESIGN AND SYNTHESIS OF MOLECULAR TWEEZER BASED ON 3-HYDROXYFLAVONE FOR THE DETECTION OF ATP: UDC 547.8 + 547-32 +547.97 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
Adenosine 5'-triphosphate (ATP) is known as a universal energy source and signaling mediator in numerous biological processes. Among the methods for its determination, molecular fluorescence probes occupy leading positions due to high sensitivity and selectivity. Recently we have shown that 31 of 33 tested flavones and quinolones of various structures give fluorescence response and can be effectively applied as the probes in aqueous solutions for detection of ATP in 1–50,000 μM range of its concentrations. To increase response parameters of a probe in respect to ATP we have synthesized N,N'-(butane-1,4-diyl)bis(2-((2-(4-(dimethylamino)phenyl)-3-hydroxy-4-oxo-4H-chromene-6-yl)oxy)acetamide, the molecular tweezer composed of two flavonol units connected by active linker. On our idea, being equipped by two planar platforms, the tweezershould demonstrate increased affinity and selectivity to ATP in a result of increased number of hydrogen bonds and increased stacking interactions. Having two NH-amide groups the amino acid linker will form hydrogen bonds with the phosphates of ATP, increasing the portion of probe-ATP complex population in the reporting conformation.In the four-step synthesis of this molecular device, starting from methyl 2-(3-acetyl-4-hydroxyphenoxy)acetateand N,N-dimethylaminobenzaldehyde, the conditions for the reaction of one-pot chalcone formation and its oxidative heterocyclization in the presence of an organic base were found, which resulted in the isolation of a target flavonol- amino acid derivative with high yields. We suggest that atmospheric oxygen was an oxidizer in this process. The obtained derivative was converted intotarget compound by dual condensation with 1,4-butane diamine.
Keywords: flavonol, molecular tweezers, ATP, oxidative heterocyclization